Teachers acceptance of wireless internet technology: An exploratory study in Perlis - Idrus, Roshdan; Azzali, Fazli (2006)
The wireless internet technology offers teachers great deals of opportunities and challenges.The purpose of this exploratory research is to study the teachers’ acceptance of the wireless internet technology in the state of Perlis. This study utilizes the Technology Acceptance Model as a model to enhance our understanding of the acceptance of wireless internet by the teachers.Findings from this study will determine the teachers’ perception toward the usefulness and ease of use of the wireless internet technology. It will also determine the teachers’ attitude and intention toward wireless internet. Findings will also find out the impact of wireless internet on the teachers’ job performance.